THE AESTHETICS OF CITY PLANNING BY CONFRONTATION OF PANDEMICS CORONAVIRUS - Sultan, Noor R; Altaweel, Maha A (Journal of Geography, Regional Planning and Development, 2025)
Objective: This study aims to analyze changes in daily life and urban activity patterns to understand new interaction mechanisms between recipients and cities, and how these circumstances reshape recipients' perceptions of cities in the absence of the usual urban rhythms. The study attempts to highlight forms of beauty that emerged or were rediscovered during the crisis. Method: The effects of epidemics on cities were examined through a historical review and critical analysis of the spread of epidemics, up to and including the Coronavirus, and their impact on urban life and development processes. Results: It was concluded that, despite the severity of the crisis, the precautionary measures were a double-edged sword as they allowed for a reconsideration of urban aesthetics from new angles, it was realized that the concept of city aesthetics is not just a normative structure with strict rules, but a concept linked to its reality (context). The crisis also encouraged us to think about the role of urban planning in the context of health crises and to consider how it can demonstrate flexibility and beauty simultaneously. This involves providing strategies and solutions that align with the nature of people's lives and the characteristics of each area. This would enhance the city's capacity to withstand crises and its ability to fulfill the fundamental needs of the population, as well as aesthetic and psychological requirements. Novelty: This crisis is a unique experience that invites us to reconsider how cities are designed and how we live in them, shifting the focus from consumers to partners in shaping their aesthetic meaning.